RELAXATION TO REDUCE ANXIETY IN PREGNANT MOTHERS - Ratri Susilaningrum; Nurul Hidayah (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
This study aims to examine the effect of relaxation in reducing anxiety in pregnant mothers. The subjects in this study were five pregnant mothers aged 21-28 years. The research method used was an experimental study with a one-group pretest-posttest research design using a purposive sampling technique. The research instrument uses the Hamilton Anxiety Rating Scale (HARS) which has been adapted into Indonesian by Setyaningsih [17]. The interventions given were breath, muscle relaxation, and visual relaxation. Based on the results of the nonparametric analysis test with Wilcoxon analysis techniques to see the difference between pretest and posttest. The results of the analysis obtained are 0, 043 the score <0, 05. These results indicate that there is a decrease in anxiety in pregnant mothers. It was concluded that the application of relaxation can reduce anxiety levels in pregnant women